Mega Sporting Events and Air Pollution: The Case of the Super Bowl - SILVA, Carlos G.; RICKETTS, Comfort F. (Journal of Environmental Management and Tourism, 2016)
In attempt to improve local economy, local officials often seek to host major sporting events. While previous studies have examined the economic costs and benefits of such events, some prospective externality costs related to changes in ambient air quality have not yet been included in those evaluations. This study focuses on the possible changes of Particulate Matter (PM10) and air quality during the Super Bowl. Particulate Matter are suspended particles which are present in the air, these particles when inhaled can lead to negative health effects. Statistical models are estimated using daily data from EPA’s Air Quality System which measures particle pollution (PM10) as well as air quality (AQI). Estimates using PM10 measurements and AQI reveal similar outcomes, although the Air Quality Index model has a better fit. Significantly higher levels of pollution are observed on Super Bowl Sunday while accounting for a variety of confounding factors. The concentration of pollution varies by distance from the stadium hosting the event, it would be beneficial for future research to have more active monitoring stations on the day of mega-events such as the Super Bowl in order to increase the ability to analyses and understand the environmental consequences of hosting the event.
Keywords: I10; Q53; Z20; Z30